2020
DOI: 10.2478/zireb-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Are Growth Led Financing Decisions Causing Insolvency in Listed Firms of Pakistan?

Abstract: We examine the relationship between growth opportunities and insolvency risk in a mediating framework through financing decisions for 330 listed firms on the Pakistan Stock Exchange (PSX) This study covers a data period of five years ranging from 2013 to 2017. Financing decisions used in this study involve capital structure decision and debt maturity decision. We applied robust clustered panel OLS regression to the data and found a negative relationship between growth opportunities and insolvency risk in all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 128 publications
1
4
0
Order By: Relevance
“…The results of our research are in line with some previous research that showed the positive impact of sales growth on enterprise solvency (Patti et al, 2015;Hussain et al, 2020) but also those that emphasized how high growth can be at the same time high risk (Bjørn & Naes, 2010;Amaral, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of our research are in line with some previous research that showed the positive impact of sales growth on enterprise solvency (Patti et al, 2015;Hussain et al, 2020) but also those that emphasized how high growth can be at the same time high risk (Bjørn & Naes, 2010;Amaral, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Enterprises with a high risk of insolvency are similar to firms with high future sales growth. Hussain et al (2020) proved a negative relationship between growth opportunities and insolvency risk. Additionally, growth opportunities harm the capital structure while debt maturity was influenced positively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The debt maturity has a significant positive impact on emerging market Z score referring to the fact that firms using larger proportion of long term debt in their debt maturity structure have lower level of insolvency risk (Adachi-Sato and Vitessonthi, 2019; Wang and Chiu, 2019). This evidence also confirms that debt maturity mediates the relationship between firm growth and insolvency risk in the proposed relationships (Hussain et al, 2020). The results also reveal that leverage maturity and PFCs have a significant impact on insolvency risk when used separately in a mediating role as depicted in models five and 6.…”
Section: Main Empirical Findingsmentioning
confidence: 54%
“…In underdeveloped economies, the business growth faces obstacles, specifically with reference to the availability of favorable loan opportunities (ICMAP, 2015). Finally, the past literature is The state owned business had a negative impact of audit quality and income growth on default risk 2 Meher & Getaneh (2019) 2011-2017 In banking sector, the Ethopian commercial banks under analysis a significant positive impact of growth measured through net income on financial entrenchment was observed 3 Hussain et al (2020) 2013-2017 This study on the contrary provrd a significant negative association between firm growth and insolvency risk in 330 firms listed at PSX. 4…”
Section: Introductionmentioning
confidence: 81%
“…Market illiquidity, together with the difficulty of creditors in coordinating their rollover decisions of a firm's short-term debt, could lead to runs on firms (Morris and Shin, 2016). Hussain et al (2020) evaluated the impact of growth-led financing decision on insolvency risk and reported that debt maturity ratio (DMR) mediates the relationship between growth opportunities and insolvency risk in non-financial listed firms in Pakistan; however, no such evidence was detected for capital structure.…”
Section: Cedu Leverage Decision and Insolvency Riskmentioning
confidence: 99%